Web-Based Student Score Application Design at Husni Thamrin Private Junior High School, Medan - Erwin; Joni; Chandra, Wenripin; Robin; Napitupulu, Normalina (Talenta Publisher, 2023)
Value data processing is one of the most important parts of school operations and activities. Husni Thamrin Medan Private Middle School, one of the schools that organizes an educational process based on the 2013 Curriculum, manages value data through manual and separate input by each teacher. It is hoped that through the development of a web application-based value management system, value data processing can be carried out more easily and integratedly. To implement the use of this application, training is needed for teachers so they can get to know the features and how to use the application.